MANAGEMENT OF ENDOCRINE DISEASE: Management of Cushing's syndrome during pregnancy: solved and unsolved questions. Issue 6 (June 2018) - Brue, Thierry; Amodru, Vincent; Castinetti, Frederic
Abstract : With fewer than 200 reported cases, Cushing's syndrome (CS) in pregnancy remains a diagnostic and therapeutic challenge. In normal pregnancies, misleading signs may be observed such as striae or hypokalemia, while plasma cortisol and urinary free cortisol may rise up to 2- to 3-fold. While the dexamethasone suppression test is difficult to use, reference values for salivary cortisol appear valid. Apart from gestational hypertension, differential diagnosis includes pheochromocytoma and primary aldosteronism. The predominant cause is adrenal adenoma (sometimes without decreased ACTH), rather than Cushing's disease. There are considerable imaging pitfalls in Cushing's disease. Aberrant receptors may, in rare cases, lead to increased cortisol production during pregnancy in response to HCG, LHRH, glucagon, vasopressin or after a meal. Adrenocortical carcinoma (ACC) is rare and has poor prognosis. Active CS during pregnancy is associated with a high rate of maternal complications: hypertension or preeclampsia, diabetes, fractures; more rarely, cardiac failure, psychiatric disorders, infection and maternal death. Increased fetal morbidity includes prematurity, intrauterine growth retardation and less prevalently stillbirth, spontaneous abortion, intrauterine death and hypoadrenalism. Therapy is also challenging. Milder cases can be managed conservatively by controlling comorbidities. Pituitary or adrenal surgery should ideally be performed during the second trimester and patients should then be treated for adrenal insufficiency. Experience with anticortisolic drugs is limited. Metyrapone was found to allow control of hypercortisolism, with a risk of worsening hypertension. Cabergoline may be an alternative option. The use of other drugs is not advised because of potential teratogenicity and/or lack of information. Non-hormonal (mechanical) contraception is recommended until sustained biological remission is obtained.